Production and composition of chemical elephant grass cv. pioneer in different heights of waste - literature review - Figueira, Danubia Nogueira [UNESP]; Neumann, Mikael; Ueno, Robson Kyoshi; Lopes Muller, Marcelo Marques; Faria, Marcos Ventura (Univ Estadual Centro-oeste, 2015)
The work aims to review studies evaluating the agronomic characteristics of elephant grass (Pennisetum purpureum, Schum) originating in Africa, it has several ways to use as hay, grazing, silage and capineira. Besides the attention for the production of dry matter per unit area is presented disseminated in several Brazilian territory, being possible to observe the production of culture, for resisting adverse weather conditions, but with average soil fertility requirement. When well managed can present fresh weight average production of 300 Mg ha(-1) is more common to find averages between 20-35 Mg ha(-1). The planting method is by cuttings and can be done in grooves or through holes. By presenting cespitose growing has rapid rise of the apical meristem, getting cleavable during grazing, one of the biggest failures of culture. The elephant grass generally has high fiber content in its composition, both neutral detergent fiber as to acid detergent fiber, 72.3% and 46.5% respectively on average, one realizes that NDF and ADF increase with advancing age, inverse role is with the amount of crude protein of fodder, which decreases with increasing age of regrowth.
Keywords: crude protein; dry matter content; harvest season and physical structure of forage